2017
DOI: 10.1186/s13568-017-0507-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving cellulase production in submerged fermentation by the expression of a Vitreoscilla hemoglobin in Trichoderma reesei

Abstract: Trichoderma reesei is well known as an industrial workhorse fungus in cellulase production. The low dissolved oxygen supply in the highly viscous medium of T. reesei remains a major bottleneck that hampers growth and cellulase production in submerged fermentation. Vitreoscilla hemoglobin (VHb) has been demonstrated to improve metabolism and protein production in different heterologous hosts under hypoxic conditions, but the use of VHb in T. reesei remains uninvestigated. This study examines the effect of VHb i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Among different microorganisms, Fusarium venenatum is the most prevalent species to be successfully utilized in food industry, and it has been applied to produce mycoprotein as food being under the trade name Quorn, and mycoprotein indicates satiation characteristics which can be a solution for obesity by enabling people to obtain a healthier diet with low fat and high fiber content [215]. It has been reported that Vitreoscilla hemoglobin has profitable advantages on improving total protein secretion and cellulase activity of Trichoderma reesei in submerged fermentation [216]. Benefits and disadvantages of Solid State Fermentation and Submerged Fermentation are presented in Table 2.…”
Section: Submerged Fermentation (Smf)mentioning
confidence: 99%
“…Among different microorganisms, Fusarium venenatum is the most prevalent species to be successfully utilized in food industry, and it has been applied to produce mycoprotein as food being under the trade name Quorn, and mycoprotein indicates satiation characteristics which can be a solution for obesity by enabling people to obtain a healthier diet with low fat and high fiber content [215]. It has been reported that Vitreoscilla hemoglobin has profitable advantages on improving total protein secretion and cellulase activity of Trichoderma reesei in submerged fermentation [216]. Benefits and disadvantages of Solid State Fermentation and Submerged Fermentation are presented in Table 2.…”
Section: Submerged Fermentation (Smf)mentioning
confidence: 99%
“…Many bacteria and fungi have been genetically engineered to express the vgb gene to improve metabolite production including metabolites such as L-DOPA, dopamine (Kurt, Aytan, Ozer, Ates & Geckil, 2009), vitamine E (Giray, 2020), phenazine (Kahraman, Aytan, Giray & Özcan, 2013) arachidonic acid (Zhang, Feng, Cui & Song, 2017), penicillin (Li, Li, Zhou, Zhao & Zhu, 2006), hypocrellin and amylase production (Gao, Deng, Guan, Liao & Cai, 2018), flavones (Zhu, Sun & Zhang, 2011), ganoderic acid (Li et al, 2016a), cellulase (Lin et al, 2017), protease and chitinase (Zhang et al, 2014). In this study, the effect of both VHb gene and various environmental conditions such as glucose, fructose, and sucrose on the production of vitamin A was investigated.…”
Section: Glucose and Sucrose Induces Production Of Vitamin A In The P...mentioning
confidence: 99%
“…The transformation of VHb has been confirmed to efficiently relief hypoxia stress in bacteria (Horng et al, 2010), yeasts (Wu and Fu, 2012), plants (Jokipii et al, 2008), and animals (Pendse and Bailey, 1994). Recently, many reports have verified that this strategy also works as an O 2 conveyor and transporter in filamentous fungi (Lin et al, 2017;Wang et al, 2019;Xu et al, 2019). Sterol regulatory element binding proteins (SREBPs) are also required for adaptation to hypoxic environment in fungi (Bien and Espenshade, 2010;Gutierrez et al, 2019).…”
Section: Introductionmentioning
confidence: 97%